2005
DOI: 10.1016/j.earlhumdev.2005.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Catch-up growth in Malawian babies, a longitudinal study of normal and low birthweight babies born in a malarious endemic area

Abstract: Malaria during pregnancy and maternal illiteracy are important maternal characteristics associated with infant undernutrition. Innovative health/literacy strategies are required to address malaria control in pregnancy in order to reduce the magnitude of its effects on infant undernutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The proportion of low birthweight infants was similar for infants in the early or late categories. A separate analysis of growth patterns of normal and low birthweight infants in this cohort showed that low birthweight babies remained shorter and lighter during infancy than their normal birthweight counterparts (Kalanda et al, 2005). Growth percentiles were parallel through infancy with no increased fall-off in low birthweight babies at the average age of introduction of complementary foods.…”
Section: Mean W/a Z-scorementioning
confidence: 73%
“…The proportion of low birthweight infants was similar for infants in the early or late categories. A separate analysis of growth patterns of normal and low birthweight infants in this cohort showed that low birthweight babies remained shorter and lighter during infancy than their normal birthweight counterparts (Kalanda et al, 2005). Growth percentiles were parallel through infancy with no increased fall-off in low birthweight babies at the average age of introduction of complementary foods.…”
Section: Mean W/a Z-scorementioning
confidence: 73%
“…Nevertheless, we have identified studies, both from Guatemala and in the international literature, with which to compare the present findings. Birth length is often part of protocols in long-term cohort studies bridging from birth through childhood and towards adulthood (40)(41)(42)(43)(44)(45) or short-term, longitudinal observational studies seeking to find correlates of early growth or health (46)(47)(48)(49)(50)(51)(52)(53) . More recently, length is measured at birth as part of studies evaluating inter-pregnancy interventions in (4) .…”
Section: Discussionmentioning
confidence: 99%
“…In a Malawian study, placental or peripheral infection at delivery was an independent risk factor for slow growth, poor weight gain and failure to thrive in the first year of life. 27 . ............................................................................................................................................... Congenital malaria affects 0.3% of infants of infected mothers in immune areas and 1-4% of infants from non-immune areas.…”
Section: Effects Of Malaria On Fetal and Neonatal Outcomementioning
confidence: 99%